Making and breaking the grid : a graphic design layout workshop - Samara, Timothy (Rockport Publishers, 2023)
Making and Breaking the Grid: A Graphic Design Layout Workshop (Third Edition) is the ultimate resource for designers who want to understand the rules of the grid, so they can get better at breaking them.